2019
DOI: 10.1007/s11705-019-1794-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-catalysis: Is it just a question of scale?

Abstract: The issues of describing and understanding the changes in performance that result when a catalyst is placed into plasma are discussed. The different chemical and physical interactions that result and how their combination might produce beneficial results for the plasma-catalytic processing of different gas streams are outlined with particular emphasis being placed on the different range of spatial and temporal scales that must be considered both in experiment and modelling. The focus is on non-thermal plasma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…A large variety of comprehensive reviews dealing with the wide field of plasma catalysis has been published during the last decades [6,7,[21][22][23][24][25][26][27][28][29][30][31]. Some of them focus on particular applications such as the oxidation of VOCs [7], while others emphasize the importance of modeling and simulation to understand plasma catalysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of comprehensive reviews dealing with the wide field of plasma catalysis has been published during the last decades [6,7,[21][22][23][24][25][26][27][28][29][30][31]. Some of them focus on particular applications such as the oxidation of VOCs [7], while others emphasize the importance of modeling and simulation to understand plasma catalysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, such mutual influences of the plasma and the catalyst were extensively discussed by Neyts et al 125,228,229 and Kim et al 219 Recent modelling investigations and characterization have provided novel insights. 230,231 This subsection sets the stage for the assessment of plasma-catalytic ammonia synthesis.…”
Section: Coupling Of Plasma and Catalystmentioning
confidence: 99%
“…However, plasma-catalyst interactions and synergies thereof are not trivial to uncover, as the underlying principles of plasma catalysis are not fully understood. 231,233,234 Various possible plasma-catalyst interactions have been proposed for ammonia synthesis, as shown in Fig. 8.…”
Section: Coupling Of Plasma and Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between plasma and catalyst is highly complex because their interaction occurs at a far-fromequilibrium state. Whitehead 26,27 described various interactions between plasma and the catalyst, effects of catalysts on the properties of the discharge, and changes in the performance of the catalyst. Neyts et al 6 reported that relatively less information is available on the factors of observed synergy because the process of plasma catalysis is highly complex.…”
Section: Introductionmentioning
confidence: 99%